Expression and Significance of Immune Checkpoints in Clear Cell Carcinoma of the Uterine Cervix - Liju Zong; Qianqian Zhang; Yuncan Zhou; Yujia Kong; Shuangni Yu; Jie Chen; Youzhong Zhang; Yang Xiang (Journal of Immunology Research)
The purpose of this study was to investigate the expression levels of the immune checkpoint proteins, programmed cell death-ligand 1 (PD-L1), B7-H3, B7-H4, and V-domain Ig suppressor of T cell activation (VISTA), as well as the significance thereof, in clear cell carcinoma (CCC) of the cervix (a rare histological subtype of cervical cancer). We also compared the expression statuses of these biomarkers in cervical CCCs with those in cervical squamous cell carcinomas (SCCs). We evaluated the expression of PD-L1, B7-H3, B7-H4, and VISTA in 50 cervical CCCs and 100 SCCs using immunohistochemical staining and investigated the associations between these markers, clinicopathologic features, and survival in patients with CCCs. Of the cervical CCC samples examined, 22%, 16%, 32%, and 34% were positive for PD-L1, B7-H3, B7-H4, and VISTA, respectively. Nineteen samples (38%) were negative for all 4 of these markers, whereas 31 (62%) expressed at least 1 marker. None of these markers was associated with the investigated clinicopathologic variables or patient survival. PD-L1, B7-H3, and VISTA were observed significantly more frequently in SCCs than in CCCs of the cervix. Our study confirmed the expression of immune checkpoint proteins in cervical CCCs and indicated their nonredundant and complementary roles. As such, our data suggest that monotherapeutic immune checkpoint blockade may not be sufficiently effective in patients with cervical CCC.